Combined effect of salinity and cadmium in the presence of other metals (Zn & Cu) and GSH on lysosomal responses in an arcid blood clam Anadara granosa - Anthony, K; Patel, B (Indian Journal of Fisheries, 2011)
Exposure of tropical arcid blood clam Anadara granosa to sublethal concentrationof Cd, Zn, Cu and GSH (Glutathione) at different salinities (16 - 32 g kg-') inducedvarious changes in the activities of the lysosomal marker enzymes - arylsulphataseand acid phosphatase. Changes in the lysosomal enzyme activity on exposureeither to Cd or GSH was inversely related to ambient salinity. Cu inhibited enzymeactivity at both salinities. Zn, however, caused no significant changes. GSHtogether with Cd reduced the enzyme activity at both salinities whereas thepresence of Zn or Cu significantly (P